The Effect of Person Job Fit and Person Organization Fit on Turnover Intention with Employee Engagement as an Intervening Variable (Empirical Study on Employess of the Sales Promoter Division of Realme Big Jember) - Cicilia Permataning Mahardika; Handriyono Handriyono; Diana Sulianti K Tobing (East Asian Journal of Multidisciplinary Research, 2023)
This research aims to determine the influence of person-job fit and person-organization fit on turnover intention with employee engagement as an intervening variable. This research is quantitative research with an explanatory type of research. The sample used was 114 respondents who were employees of the sales promoter division of Realme Big Jember using a simple random sampling technique. The data collection method used a questionnaire and then analyzed using the SEM-PLS method via SmartPLS 3. The results of the study stated that 1) Person job fit did not affect turnover intention, 2) Person job fit affected employee engagement, 3) Person organization fit affected turnover intention, 4) Person organization fit influences employee engagement, and 5) Employee engagement does not influence turnover intention. Another conclusion regarding the indirect influence of employee engagement is that it is unable to mediate the influence of person-job fit and person-organization fit on turnover intention.